Trends in the availability of community-based home visiting services for oldest-old in China, 2005–2018 - Yukuan Gao; Ruibo He; Zhong Li; Dongfu Qian; Peiyin Hung; Mingsong Xuan (BMJ Open)
Objectives This study aims to examine trends in neighbourhood availability of community-based home visiting services (CHVS) (ie, coverage by local primary healthcare providers) over time and disparities in service availability according to individual characteristics using nationwide data of oldest-old individuals (age >80) in China.Design Repeated, cross-sectional study.Setting This study derived nationally representative data from the 2005–2018 Chinese Longitudinal Health Longevity Survey.Participants A final analytical sample of 38 032 oldest-old individuals.Primary outcome measures Availability of CHVS was defined as having home visiting services in one’s neighbourhood. Cochran-Armitage tests were used to test linear trends in the proportions of oldest-old with service availability. Weighted logistic regression models were used to examine variations in service availability across individual characteristics.Results Of 38 032 oldest-old individuals, availability of CHVS decreased from 9.7% in 2005 to 7.8% in 2008/2009, followed by continual increases to 33.7% in 2017/2018. These changes were similar between rural and urban oldest-old. After accounting for individual characteristics, in 2017/2018, compared with their counterparts, urban residents who had white-collar jobs before retirement and those residing in Western and Northeast China were less likely to have service availability. Oldest-old with disabilities, those living alone and those with low incomes did not report having greater availability of CHVS in either 2005 or 2017/2018.Conclusions Despite the increasing service availability over the past 13 years, persistent geographical disparities in the availability of CHVS remain. As of 2017/2018, only one in three oldest-old in China reported having service availability, which raises concerns regarding continuity of care across different settings of services for those most in need, especially those living alone or with disabilities. National policies and targeting efforts are necessary to improve the availability of CHVS and reduce inequity in service availability for optimal long-term care to the oldest-old population in China.